2006
DOI: 10.1248/cpb.54.1113
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxic Activity of Benzo[a]pyrano[3,2-h] and [2,3-i]xanthone Analogues of Psorospermine, Acronycine, and Benzo[a]acronycine

Abstract: Condensation of 2-hydroxy-1-naphthalenecarboxylic acid with phloroglucinol afforded 9,11-dihydroxy-12H-benzo[a]xanthen-12-one (6). Construction of an additional dimethylpyran ring onto this skeleton, by alkylation with 3-chloro-3-methyl-1-butyne followed by Claisen rearrangement, gave access to 6-hydroxy-3,3-dimethyl-3H,7H-benzo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Especially, the effective inhibitory activity against human cancer cell lines has attracted considerable attention. [6][7][8][9][10] The preliminary work has highlighted the high potentials of xanthones as a promising building motif for the development of a new class of potent anticancer drugs.…”
mentioning
confidence: 99%
“…Especially, the effective inhibitory activity against human cancer cell lines has attracted considerable attention. [6][7][8][9][10] The preliminary work has highlighted the high potentials of xanthones as a promising building motif for the development of a new class of potent anticancer drugs.…”
mentioning
confidence: 99%
“…Materials The benzoxanthones 1 and 2 were prepared according to the literatures [13][14][15] with some improvement. Calf thymus DNA (ct DNA) and ethidium bromide (EB) were obtained from Sigma Chemical Co. All the measurements were carried out in doubly distilled water buffer containing 5 mM Tris and 50 mM NaCl, and adjusted to pH 7.4 with hydrochloric acid.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, the effective inhibitory activity against human cancer cell lines has attracted considerable attention and many xanthone derivatives with excellent anticancer activity have been obtained. [12][13][14][15] For example, Shen et al reported xanthone derivatives substituted by six different groups, of which the piperidinylethoxy-substituted xanthone could efficiently prohibit the growth of cancer cells. 16 Although preliminary work has highlighted the high class of the potent anticancer potentials of xanthone as a promising building motif for the development of new drugs, more efforts on structural modification of xanthone as well as on their pharmacological activity should be realized.…”
Section: Introductionmentioning
confidence: 99%